Analyzing the Impacts of Implementing Cambridge Curriculum on Students’ English Academic Achievement - Nazizah, Mailatun; Lisan, Khusnul Harsul; Arta, Berli (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
The Cambridge Curriculum, which is typically implemented in international standard schools, is the primary focus of this investigation. Nevertheless, Assalafiyah Islamic Junior High School, a boarding school, has incorporated the Cambridge Curriculum into its educational program. The purpose of this study is to determine the impact of the implementation of the Cambridge Curriculum on Students' English Academic achievement in VIII Graders of Assalafiyah Islamic Junior High School Mlangi Yogyakarta. The academic performance of eighth-grade students was compared under two distinct curricula: the 2013 Curriculum and the Cambridge Curriculum, using a mixed-methods approach. The grades of 89 students in three classes (A, B, and C) were analyzed to collect quantitative data under both curricula. Further, interviews were conducted with 12 participants from the Islamic Junior High School in Mlangi, Yogyakarta, including 6 male students, 5 female students, and 1 teacher, for the qualitative analysis. The results of this study indicated that the application of the Cambridge Curriculum on Students' English Academic achievement of VIII graders had a very good impact. The students increased in terms of academic scores when learning using Cambridge Curriculum compared to the previous Curriculum. Besides, they were more enthusiastic in participating in the English lessons in class.